Inside Back Cover: Multi‐shelled Hollow Metal–Organic Frameworks (Angew. Chem. Int. Ed. 20/2017). Issue 20 (4th April 2017) - Liu, Wenxian; Huang, Jijiang; Yang, Qiu; Wang, Shiji; Sun, Xiaoming; Zhang, Weina; Liu, Junfeng; Huo, Fengwei
Abstract : Hollow metal–organic frameworks (MOFs) with sophisticated structures, such as multiple shells, are promising materials that can not only enhance the properties of MOFs but also endow them with new functions. In their Communication onpage 5512 ff., J. Liu, F. Huo et al. report a strategy to obtain multi‐shelled hollow MOF crystals that show significantly enhanced catalytic activity during styrene oxidation.